The Implementation of Language Experience Approach (LEA) in Teaching Speaking: A Case Study - Ahlan Fadil Basra; Sri Suci Suryawati; Sugeng Riyadi (Universitas Islam Negeri Palopo, 2026)
This study examines the implementation of the Language Experience Approach (LEA) in teaching speaking to junior high school students. This study was conducted in response to students' common experiences in using this approach to overcome their barriers in speaking English, such as low participation, nervousness, and speaking difficulties. LEA is considered an efficient strategy because it allows students to learn more actively based on their experiences, which makes them more actively involved in speaking in class. The purpose of this study is to investigate how LEA is implemented in English speaking lessons and to describe the stages, procedures, and responses of teachers and students' experiences when using this approach. The sampling technique used was purposive sampling. Data collection techniques used were observation, interviews with teachers and students, and documentation. The instruments used were observation sheets, interview guides, audio recordings, and media documentation notes developed based on relevant indicators related to LEA implementation. For data analysis, this study used the Triangulation analysis model by Miles and Huberman, with data reduction, data presentation, and closing by drawing conclusions. The results of this study are expected to provide insight into a clear picture of its implementation.